Geometric and kinematic evolution of the Jiali fault, eastern Himalayan Syntaxis. (1st June 2021) - Zhang, Ling; Liang, Shiming; Yang, Xiaoping; Gan, Weijun; Dai, Chenglong
Graphical abstract: Highlights: New GPS data in the Eastern Himalayan Syntaxis. The strike-slip rates of the western and middle segments of the Jiali fault are low. The eastern segment of the Jiali fault no longer accommodates strike-slip motion. Decrease in the slip rate of the Jiali fault coincides with new faults emergence. The eastern segment of the Jiali fault seems to rotate clockwise. Abstract: Large strike-slip faults play an important role in slip partitioning of the oblique convergence between the Indian plate and the Eurasian plate. The Karakorum-Jiali fault zone (KJFZ) is regarded as the southernmost major fault in the strike-slip faults system of the Tibetan plateau. The significance of the Jiali fault as the southern boundary of the eastward extrusion of the Tibetan plateau remains subject to debate due to the wide disagreements in its strike-slip rate. There is also a huge mismatch between its previously predicted low slip rate and the accommodation of the most significant compression in the frontal Eastern Himalayan Syntaxis. New GPS measurements suggest that the dextral strike-slip rate of the western segment, the middle segment, and the western part of the eastern segment of the Jiali fault is 5.0 ± 0.5 mm/yr, 2.4 ± 0.8 mm/yr, and 3.8 ± 0.9 mm/yr, respectively. As for the eastern segment of the Jiali fault, based on a two-dimensional elastic dislocation model, we search for the optimal solutions of the strike-slip rates along its two branch faults. They no longer accommodate strike-slip motion. But the diffuse active fault zone between the Mishimi and Puqu fault, inferred by the distribution of small earthquakes and systematic geologic mapping, may accommodate the strike slip motion with an estimated rate less than 5 mm/yr. Thus, it is predicted to have taken place the eastern segment. The eastern segment of the Jiali fault appears to have horizontally rotated clockwise around the Namche-Barwa Syntaxis.